Influence of plant growth regulators on content of Azadirachtin and proteome profile in neem callus under jasmonic acid and salt stress conditions / Sharmilla Ashokhan - Sharmilla, Ashokhan (2022)
For centuries, neem (Azadirachta indica L.) has been utilized as a primary source of medicine due to its antimicrobial, larvacidal, antimalarial, and antifungal properties. Its potential as an effective biopesticide has recently garnered attention, especially towards efficient and continuous production of its bioactive compounds. The present study investigated the effect of the plant growth regulators (PGRs) thiadiazuron (TDZ) and 2, 4-dichlorophenoxyacetic acid (2, 4-D) on the induction of callus and subsequent comparative proteomic analyses upon abiotic stress (salt and jasmonic acid (JA)) induction. The callus cultures were initiated from leaf and petiole explants and cultured on Murashige and Skoog (MS) medium supplemented with TDZ (0.2–0.6 mg/L) and 2,4-D (0.2–0.6 mg/L), either applied individually or in combination. Callus was successfully induced from both explant types at different rates, where media with 0.6 mg/L of TDZ resulted in the highest fresh weight (3.38 ± 0.08 g). A culture duration of six weeks resulted in the production of green, brown and cream-coloured callus. The green callus contained the highest amount of anthocyanin, chlorophyll and carotenoid and total phenolic content compared to brown and cream callus. Green callus also exhibited the highest antioxidant potential plus the highest accumulation of azadirachtin (AZA) at 214.53 ± 33.63 mg/G dry weight (DW). However, small amounts of AZA was detected in brown and cream callus. Green callus also profoundly exhibited active cytotoxic activity against SKOV-3 cells. In a further abiotic stress induction and comparative proteomics experiment, green callus was subjected to 0.5 % (w/v) of NaCl and 5 mg/L of JA, which was identified as the optimum concentration for stress treatment. Four protocols derived from either TCA/acetone and/or phenol procedures were evaluated to determine the optimum protein extraction method for neem callus. The TCA-acetone method with inclusion of PVPP recovered highest amount proteins, with superior gel resolution and minimal streaking. The 2-DE technique applied to discover stress-response proteins revealed that proteins associated with oxidoreduction, energy, transcriptional, stress response, respiration and cell division were differentially regulated under salinity stress treatment. Meanwhile, the expression of proteins classified in the group of energy, photosynthesis, protein synthesis, oxidoreduction, and post-transcriptional regulation was altered in the JA-stressed callus. Combining with these outcomes, the accumulation of AZA was noticeably reduced in salt and JA-treated callus, suggesting these tested stress parameters were not effective in improving AZA production in the neem callus. Overall, the present analysis provides valuable information on applying plant tissue culture as an alternative for sustainable production of major bioactive constituents in A. indica. Together, the proteomic results brought forward a possible fundamental representation of the mechanism associated with the salt and JA tolerance in the neem callus.